Analysis of hairtail (Trichiurus sp.) fishing by handlines in Palabuhanratu Bay, West Java - Mohammad Imron; Didin Komarudin; Arik Permana; M Fedi Sondita; Ari Purbayanto (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2021)
The waters of Palabuhanratu Bay are fertile and rich with fish resources. For a long time, fishermen have used the fish resources in these waters. Hairtail (Trichiurus sp.) was one of the fish resources in Palabuhanratu Bay that caught by fishermen using handlines. Fishery production landed at Palabuhanratu Fishing Port in 2019 was 5,414,240 kg with a total hairtail production of 314,107 kg. The problem raised in this study was knowing the right hairtail fishing season so that it provides optimum benefits for fishermen. In addition, knowing potential fishing areas could assist fishermen in choosing their fishing time and fishing ground. The purpose of this study was to describe the hairtail fishing unit, to analyze the catch composition of handline, to analyze the fishing season patterns of hairtail fish, and to analyze hairtail fishing ground in Palabuhanratu bay. The results of the analysis showed that the fishing season for hairtail (Trichiurus sp.) in the waters of Palabuhanratu Bay lasts for 5 years with the peak in October. However, the reality is that fishing operations can be carried out throughout the year. The average catch per unit effort (CPUE) of hairtail (Trichiurus sp) duringfishing seasons was 11.32 kg/trip in 2019. The potential fishing ground was in the waters of West Ujung Genteng, Southern waters of Sawarna, Southern waters of Karanghawu and the waters of West Ujung Karang Bentang.Keywords:Fishing season patternHairtail fishFishing groundPalabuhanratu Bay